One person had some money. he gave one rupee to beggar and half of the remaining money was spent for buy something. same thing happened second day he gave one rupee to beggar from remaining money of first day. this continued on the six day he had 0 rupee, then how much money he had on first day?

Check your answer:-

Click here to See Solution
He was left with 0 rupee on sixth day, this means he had only 1 rupee on sixth day.

so he had 1*2 + 1 = 3 on 5th day

on 4th day start 3*2 +1 = 7

on 3rd day start 7*2 + 1 = 15

on 2nd day start 15*2 + 1 = 31

on first day start 31*2 + 1 = 63

briancordierhtc says

This is written horribly. It should be 31. Day 1 (31-1)/2=15. Day 2 (15-1)/2=7. Day 3 (7-1)/2=3. Day 4 (3-1)/2=1. Day 5 (1-1)/2=0. Day 6 = no money. When day 5 started he had one rupee. They asked what he started the day with on day 1. So, to stay parallel, on day 6, They should start the day with 0 rupee. They expect people to extrapolate what they mean. They should clearly state, “…at the end of day 6, he had 0 rupee.”

vishal sorathiya says

63

Sandeep Vashisth says

Number can be achieved easily (one can implement the same scenario in MS-excel and keep changing the initial value). I am interested in how this can be solved out. So any one can please share that formula/solution?

briancordierhtc says

To get the answer you want, you need to end with a 1 on the last day. So each day you need to double it and ad one. I.e. The day before he would have (2*1)+1=3. The day before that, he would have (2*3)+1=7. So forth and so on.

Sourabh Bansal says

63